Efektivitas Metode Pembelajaran Student Teams Achievement Divisions Terintegrasi dengan Praktik Aktif dalam Meningkatkan Hasil Pembelajaran Kognitif Pelajaran Akhlak untuk Siswa Kelas 10 di SMA Labschool Rawamangun - Kamila Rahma Shalehah Kamila; Sari Narulita Sari; Muhamad Ridwan Effendi Muhamad (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research originated from field findings indicating that student outcomes had not reached the mastery level, students experienced difficulty understanding the subject of Akhlak, specifically the theme of avoiding Akhlak Mazmumah or disgraceful morals, and the use of teaching methods that were less appropriate or innovative. Consequently, this study aims to examine the effect of implementing the Student Teams-Achievement Divisions learning method based on active practice during the learning process in improving the cognitive learning outcomes of 10th-grade students in the Akhlak subject during the first semester at SMA Labschool Rawamangun. The method used in this research utilized a quantitative approach of the quasi-experimental type with a non-equivalent control group design using a purposive sampling technique. The research sample consisted of 20 students in the experimental class and 15 students in the control class. The research results using the Mann-Whitney U test indicated a significant difference between the learning outcomes of students who received the STAD method treatment integrated with active practice and those without treatment using the direct instruction method commonly used by teachers, with a Sig. (2-tailed) value of 0.000 <0.05. Strengthened by the N-Gain test results, where the experimental class score was 0.65 > 0.30, categorized as medium with an interpretation of moderately effective, and the control class score was 0.28 < 0.30 categorized as low with an interpretation of ineffective. Therefore, H1 is accepted and H0 is rejected, providing treatment using the STAD method integrated with active practice in the experimental class is more effective and has a significant effect in improving students' cognitive learning outcomes compared to the method commonly used by teachers, namely direct instruction in the control class.